Sesiones Fitness Modalidad Pilates Para Fomentar La Autoestima En Las Internas Condenadas De La Reclusión De Mujeres Armenia (2014)
Physical education as a tool and integrating element allows us to form through movement, and it is positive element in the search for effective and aware development of body movement in the subject`s interaction with the environment in which he operates, in this case, through physical activities aimed to foster self-esteem. Health is part of these sciences on which physical education has a large impact, especially if it refers to mental health “self-esteem”, which is the foundation of psychological health. In Colombia, the population which is most affected in terms of low levels of self-esteem is the prison population. It means that people with poor living conditions until March 2013, were 116.000, and it is not favorable for promoting individual self-fulfillment in prisoners. From this problematic, this degree work was creating with the aim of attending the low levels of self-esteem through exercise. This degree work is entitled “Fitness sessions, Pilate’s modality to foster self- esteem in convicted women of RM Armenia in 2013”. The practical work has the advantage of biological welfare which is promoted by the practice of physical exercise on mental health. And it is also joined to the performance of 75 sessions of Pilates oriented to foster building self-esteem, and motivational activities. To conclude that exercise training aimed at building self-esteem is a tool that can positively influence this population.